Synthesis and spectroscopic characterization of alkali–metal intercalated ZrSe2. Issue 9 (7th December 2017) - Nikonov, Konstantin; Ehlen, Niels; Senkovskiy, Boris; Saigal, Nihit; Fedorov, Alexander; Nefedov, Alexei; Wöll, Christof; Di Santo, Giovanni; Petaccia, Luca; Grüneis, Alexander
Abstract : We report on the synthesis and spectroscopic characterization of alkali metal intercalated ZrSe2 single crystals. Abstract : We report on the synthesis and spectroscopic characterization of alkali metal intercalated ZrSe2 single crystals. ZrSe2 is produced by chemical vapour transport and then Li is intercalated. Intercalation is performed from the liquid phase ( via butyllithium) and from the vapour phase. Raman spectroscopy of intercalated ZrSe2 reveals phonon energy shifts of the Raman active A1g and Eg phonon modes, the disappearance of two-phonon modes and new low wavenumber Raman modes. Angle-resolved photoemission spectroscopy is used to perform a mapping of the Fermi surface revealing an electron concentration of 4.7 × 10 14 cm −2 . We also perform vapour phase intercalation of K and Cs into ZrSe2 and observe similar changes in the Raman modes as for the Li case.